(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Overweight is becoming a major public health problem in the modern world. The prevalence of this disorder is steadily growing globally affecting majority of the population, especially children resulting from a paradigm shift in the lifestyle of the modern generation. On the other hand, dental caries is a dental problem worldwide. The magnitude of the disease is increasing in recent years among child population due to modern dietary habits. Aim: This study aims to find an association between overweight and dental caries among 8–13-year-old school children in Ghaziabad, India and to analyze the role of demographic variables on the association. Materials and Methods: A total of 343 school children aged 8–13 years were recruited from four randomly selected schools located at four different geographic zones of Ghaziabad city. Body mass index for age was recorded for assessing overweight using Centers for Disease Control growth curves. Dental caries was recorded based on the WHO criteria 1997. Data were analyzed. P < 0.05 was considered statistically significant. Results: The prevalence of dental caries among school children was 54.6% and overweight was 30.8%. A significant association between dental caries and overweight was observed (P < 0.05). Socioeconomic status was found to be the predictor of dental caries among overweight children. Conclusion: There was an association between overweight and dental caries in school children. Overweight and dental caries have common risk determinants and require a comprehensive multidisciplinary approach by health professionals.